Mutation spectrum of Duchenne muscular dystrophy patients in Indian population - Mathur, Priyanshu; Agarwal, Ansh; Goyal, Kashish; Mathur, Avisha (Indian Journal of Child Health, 2020)
Background: Duchenne muscular dystrophy (DMD) is the most common X-linked neuromuscular disorder in children. Since the novel, DMD therapies are mutation-specific, so detection of mutation is of paramount importance in planning the treatment of DMD patients. Objective: The objective of this study was to find different mutations present in DMD patients in Indian population. Materials and Methods: This study was a hospital-based retrospective observational study conducted from December 2018 to December 2019 in the pediatric department of a tertiary hospital of western India. A total of 52 children age 2–16 years, presenting with progressive muscle weakness, were included in the study. DMD multiplex ligation-dependent probe amplification (MLPA) for 79 exons was done for detection of deletion/duplication for all patients. Whole DMD gene sequencing was done for those who were found MLPA negative for DMD gene mutation (deletion/duplication). Results: Our study states that most of the DMD patients presented with deletions (84%) or duplications (11%) in the dystrophin gene, and remaining due to point mutation. The study shows that most of the mutations occur due to deletions (67.30%) in DMD gene at distal hotspot 45–52 exons and deletions (15.38%) in DMD gene at proximal hotspot 10–19 exons. In addition, to expanding the mutational spectrum of DMD, these results establish improved mutations data in the Indian population. Conclusion: The novel developed therapies for DMD are mutation-specific, so molecular diagnostic tests are very important in diagnosis and categorization for the prevalent mutations in the Indian population.